Birth injuries in late preterm and term neonates after instrumental delivery: a prospective study on short-term and developmental outcomes - Elgharbawy, Fawzia Mohamed; Abedin, Sarfrazul; Albedaywi, Rajai; Rahoma, Hoda; Khatib, Hakam; Khedr, Abdelkhalk; Nazdaf, Hakeem; Alshami, Abdulla Asa'd; Habboub, Lina; Bayoumi, Mohammad A. A.; Elmalik, Einas E.; Gad, Ashraf (Frontiers in Pediatrics, 2025)
BackgroundInstrumental vaginal delivery is a common obstetric procedure with potential neonatal complications. This study evaluated birth injuries and neurodevelopmental outcomes in neonates born at ≥35 weeks’ gestation following instrumental vaginal delivery.MethodsA prospective observational cohort conducted over 2 years (2021–2022) at Al Wakra Hospital, Qatar to assess birth injuries, neonatal intensive care unit (NICU) admission rates, and neurodevelopmental outcomes at 18 months in neonates born via instrumental delivery.ResultsThe study included 390 neonates born via instrumental delivery, with 84 birth injuries occurring in 80 neonates (20.5%). Cephalohematoma was the most common injury (43/84, 51.2%), followed by subgaleal hemorrhage and bone fractures (9/84, 10.7%) and intracranial hemorrhage (2/84, 2.38%). One neonatal death was associated with the combined use of vacuum and forceps. Birth injuries were more frequent with the combined use of vacuum and forceps (aOR 4.1, p < 0.001), labor induction (aOR 2.2, p = 0.010), and showed a trend toward increased risk with >3 instrument applications (aOR 2.2, p = 0.067). NICU admission occurred in 25.3% of neonates, with significantly higher rates in those delivered using both vacuum and forceps (18.2% vs. 5.8%, p < 0.001). Neurodevelopmental assessment was performed on 289 infants, of whom 28 (9.68%) had abnormal outcomes. The communication domain was most affected (67.8%, 19/28), followed by personal-social (28.6%, 8/28), fine motor (21.4%, 6/28), problem-solving (17.9%, 5/28), and gross motor skills (10.7%, 3/28). One infant was affected in all domains. The combined use of vacuum and forceps was an independent risk factor for abnormal neurodevelopmental outcomes (aOR 3.87, p = 0.019).ConclusionInstrumental vaginal delivery carries risks of birth injuries and neurodevelopmental challenges. Skilled application, careful assessment of indications, and long-term follow-up are essential to minimize complications and ensure optimal outcomes.